Estudo e validação de modelos de malha metálica para fins de simulação computacional de equipamentos de classificação e separação mecânica de materiais particulados sólidos - Lopes, Ícaro de Ângelis (2022)
Mechanical classification and separation are an ever-present activity in a myriad of industries: very much present in mining and fertilizer industries, as well as in pharmaceutical and food production and processing ones. Integral part of the mechanical separation process is the woven screen, usually metallic, utilized as a mean of particle gradation; however, there’s more: the screen is, in many ways, the central piece of every aspect involved in mechanical separation. Therefore, it is necessary to dive deeper into its characteristics, especially the ones related to its dynamic behavior. The proposed research goes in that direction, revising available models in certain specific areas - very prolific in this topic is the ballistic field of study with regards to textile woven materials, as are the ones utilized in mechanical separation. The work is not limited to revising the theory, but it also proposes the implementation of a convenient model - in this case, a homogenized continuous one, with orthotropic characteristics. To that end, benchwork and experimental methodologies are developed, as well as the necessary computational tools for the analysis: in view of the application of those methods in the industry, all tools were developed in open-source or low-cost software. As an example, it was used the open-source matrix laboratory GNU Octave® and the low-cost finite elements software Mecway®. In that sense, the study performed consist of obtaining the equivalent physical properties - elasticity and shear modulus, and Poisson coefficient - that would bring the model to behave in a similar manner to the real object. The proposed methodology for acquiring the model’s mechanical properties can be summarized to a minimization problem - utilizing the particle-swarm optimization heuristics optimizer (PSO) - between the difference of the experimental and modeled dynamic response, through its modal properties: natural frequency, mode shapes and damping factor. All those aspects are contained in what is called analytical and experimental modal analysis. In that regard, it is a dynamic way of obtaining the mechanical properties of the system, which differs from the usual static one. To analyze the mechanical property extraction methodology efficacy, a computational validation procedure was elaborated and has shown to be a success: the methodology can adjust the system’s dynamical response to the reference used and obtain the mechanical properties sought. At the end of the study, a review of the experimental responses of the screen is provided, in which its complex behavior is made clear, and, because of that, certain aspects of the experimental methodologies used, and analysis made, are lacking. That, however, it is not an impediment to the conclusion, based on the results obtained, that the orthotropic homogenized continuous model can synthesize part of the complex characteristics of a metallic woven screen.